An overview of green corrosion inhibitors for sustainable and environment friendly industrial development. Issue 7 (3rd April 2021) - Hossain, Nayem; Asaduzzaman Chowdhury, Mohammad; Kchaou, Mohamed
Abstract: Corrosion wreaks havoc on our properties, our lives, and environment. So, prevention of corrosion is of the utmost importance. Inorganic inhibitors are used to prevent corrosion, but these are toxic. Therefore, environment-friendly inhibitor is necessary. Green corrosion inhibitors are a probable solution to this. Their demand both environmentally and economically, is increasing. This review article briefly deals with different types of corrosion prevention methods, various green inhibitors with their source and methods of their efficient applications. The working principle of green inhibitors in different media is also explained. Corrosion determination methods are briefly discussed. Of course, the economic significance of these inhibitors has been debated. In the end, considering the current research gaps, future research directions are put forward.